Komunikasi Organisasi Pimpinan Dengan Karyawan Dalam Menjaga Kualitas Produksi Karet di PT. Bridgestone Sumatra Rubber Estate - Diva Cinta Tiara Angela (Universitas Muhammadiyah Sumatera Utara, 2026)
This research is motivated by the complexity of the work system at PT. Bridgestone Sumatera Rubber Estate, where coordination between leaders and employees in the Quality Control (QC) Department is a determining factor in product quality consistency. This study aims to describe the effectiveness of organizational communication between leaders and employees in maintaining rubber production quality at PT. Bridgestone Sumatera Rubber Estate. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving one QC Department manager and four QC employees. Data were analyzed through data reduction, data presentation, and conclusion drawing. The findings reveal that organizational communication runs effectively through four functions: informative through shift briefings, visual discussions, and WhatsApp groups; regulative through participatory SOP socialization based on flowcharts; persuasive through a diagnostic approach when procedural violations occur; and integrative through a two-way communication system formalized in shift reporting forms. The notable finding of this study is the application of the HORENSO system (Houkoku, Renraku, Soudan), which makes communication responsibility not merely about delivering a message but ensuring the message is understood by the recipient, as well as the SPT procedure (Stop, Call, Wait) as a standardized emergency communication mechanism. This research concludes that structured, two-way organizational communication grounded in a strong work culture directly contributes to the success of rubber production quality control.This research is motivated by the complexity of the work system at PT. Bridgestone Sumatera Rubber Estate, where coordination between leaders and employees in the Quality Control (QC) Department is a determining factor in product quality consistency. This study aims to describe the effectiveness of organizational communication between leaders and employees in maintaining rubber production quality at PT. Bridgestone Sumatera Rubber Estate. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving one QC Department manager and four QC employees. Data were analyzed through data reduction, data presentation, and conclusion drawing. The findings reveal that organizational communication runs effectively through four functions: informative through shift briefings, visual discussions, and WhatsApp groups; regulative through participatory SOP socialization based on flowcharts; persuasive through a diagnostic approach when procedural violations occur; and integrative through a two-way communication system formalized in shift reporting forms. The notable finding of this study is the application of the HORENSO system (Houkoku, Renraku, Soudan), which makes communication responsibility not merely about delivering a message but ensuring the message is understood by the recipient, as well as the SPT procedure (Stop, Call, Wait) as a standardized emergency communication mechanism. This research concludes that structured, two-way organizational communication grounded in a strong work culture directly contributes to the success of rubber production quality control.